How Camera Changes and Information Introduced Affect the Recognition of Public Service Announcements: A Test Outside the Lab. (October 2019) - Hendriks Vettehen, Paul; Kleemans, Mariska
This study investigated the impact of formal features on the recognition of televised public service announcements in a real-life setting. Recognition percentages of 193 public service advertisements (PSAs) derived from campaign evaluation studies were related to content analysis data of the ads. Regression analyses showed that formal features of PSAs accounted for 5% to 7% of the variance in PSA recognition. More specifically, the analyses showed that increasing the number of camera changes in PSAs slightly increases PSA recognition if the amount of information introduced by these camera changes is small, but increasing the number of camera changes tends to decrease PSA recognition substantially as the amount of information introduced by these camera changes increases. This finding implies that PSA producers should be reluctant in introducing much new information through fast-paced messages. Moreover, these results indicate that earlier findings observed in controlled, experimental settings do have ecological validity.